THE EFFECTIVENESS OF COOPERATIVE LEARNING MODEL TYPE TEAMS GAMES TOURNAMENT (TGT) ON LEARNING OUTCOMES ON THE MATERIAL OF RATIONALIZING THE DENOMINATOR OF ROOT FORM - Nurhaliza, Nabila; Yestina, Ratna; Mulyani, Agis; ., Supratman (Universitas Sembilanbelas November Kolaka, 2023)
Team Games Tournament (TGT) learning is well prepared with the right procedures, it will be better than conventional methods such as lectures that tend to be monotonous. This encourages researchers to conduct research with the title